Poor households’ experiences and perception of user fees for healthcare: a mixed-method study from Ethiopia - Barnett, I; Tefera, B (Young Lives, 2010)
Ethiopia has one of the worst health outcomes in the world. In recent years, a new health policy resulted in some improvements in the population’s health and a new health financing strategy led to critical changes in the financing structure of healthcare. However, user fees for healthcare remain an important element of healthcare financing. This study explored perceptions, attitudes and experiences with user fees at public health facilities among poor male and female household members. The objectives were to investigate (1) how poor households’ members experience user fees at public health facilities and (2) how user fees influence health-seeking behaviours of poor household members. The study used quantitative data from Round 2 of the Young Lives study and qualitative data from a substudy in four sites. We found that user fees can present a substantial psychological and financial burden and are one of the barriers to healthcare use, especially for poor households. For some families the costs of a sudden health shock combined with loss of income and assets can lead to indebtedness, distress asset sales and hardening of poverty cycles. Our findings suggest that pre-payment and risk-sharing mechanisms such as the traditional Eders or health tax might be an accepted and sustainable alternative to user fees and protect against impoverishment in case of major health events. To make cost-sharing for healthcare more equitable, it also needs to be based on income to be truly in accordance with ‘ability to pay’.